Transparency: the emerging third dimension of Open Science and Open Data - Lyon, Liz (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
This paper presents an exploration of the concept of research transparency. The policy context is described and situated within the broader arena of open science. This is followed by commentary on transparency within the research process, which includes a brief overview of the related concept of reproducibility and the associated elements of research integrity, fraud and retractions. A two-dimensional model or continuum of open science is considered and the paper builds on this foundation by presenting a three-dimensional model, which includes the additional axis of ‘transparency’. The concept is further unpacked and preliminary definitions of key terms are introduced: transparency, transparency action, transparency agent and transparency tool. An important linkage is made to the research lifecycle as a setting for potential transparency interventions by libraries. Four areas are highlighted as foci for enhanced engagement with transparency goals: Leadership and Policy, Advocacy and Training, Research Infrastructures and Workforce Development.